The co-occurrence of correct and incorrect HIV transmission knowledge and perceived risk for HIV among women of childbearing age in El Salvador - London, Andrew S. (2000)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 2000. Este documento es privado debido a limitaciones de derechos de autor.